PENGARUH PELATIHAN SELF LEADERSHIP TERHADAP RESILIENSI KERJA PADA KARYAWAN GEN Z DI PERUSAHAAN BERBASIS TEKNOLOGI DIGITAL - Dewi Handayani Harahap; Amin Al Adib; Eni Rohyati; Fx. Wahyu Widiantoro (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Changes in work systems within digital technology-based companies require employees, particularly Generation Z, to possess strong adaptive capacity and psychological resilience to cope with increasingly complex workplace demands. Although numerous studies have examined self-leadership in relation to employee performance and work engagement, experimental evidence regarding the effectiveness of self-leadership training in enhancing work resilience remains limited. This study aimed to examine the effect of self-leadership training on improving work resilience among Generation Z employees in digital technology-based companies. The study employed a quantitative approach using a one-group quasi-experimental pretest–posttest design. The participants consisted of 15 Generation Z employees selected through purposive sampling. Data were collected using a work resilience scale that had demonstrated satisfactory validity and reliability, and were analyzed using a paired-sample t-test after meeting the assumptions of normality and homogeneity. The findings revealed a significant improvement in work resilience following the training (t = −3.611; p = 0.001), with the mean score increasing from 58.27 in the pretest to 65.73 in the posttest. These results indicate that self-leadership training is an effective psychological intervention for strengthening the work resilience of Generation Z employees. The novelty of this study lies in providing experimental evidence of the effectiveness of self-leadership training in enhancing work resilience among Generation Z employees in digital technology-based companies. Furthermore, the findings offer both theoretical and practical contributions to organizational psychology by presenting an adaptive human resource development strategy to support sustainable organizational performance. ABSTRAK Perubahan lingkungan kerja pada perusahaan berbasis teknologi digital menuntut karyawan, khususnya Generasi Z, memiliki kemampuan beradaptasi dan ketahanan psikologis yang memadai untuk menghadapi tekanan kerja yang semakin kompleks. Meskipun berbagai penelitian telah mengkaji self-leadership dalam kaitannya dengan kinerja dan keterlibatan kerja, bukti empiris mengenai efektivitas pelatihan self-leadership dalam meningkatkan resiliensi kerja melalui pendekatan eksperimen masih relatif terbatas. Penelitian ini bertujuan menganalisis pengaruh pelatihan self-leadership terhadap peningkatan resiliensi kerja pada karyawan Generasi Z di perusahaan berbasis teknologi digital. Penelitian menggunakan pendekatan kuantitatif dengan desain quasi-experimental satu kelompok pretest–posttest. Subjek penelitian berjumlah 15 karyawan Generasi Z yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui skala resiliensi kerja yang telah memenuhi uji validitas dan reliabilitas, kemudian dianalisis menggunakan paired sample t-test setelah memenuhi asumsi normalitas dan homogenitas. Hasil analisis menunjukkan adanya peningkatan resiliensi kerja yang signifikan setelah pelatihan (t = −3,611; p = 0,001), dengan rata-rata skor meningkat dari 58,27 pada pretest menjadi 65,73 pada posttest. Temuan ini membuktikan bahwa pelatihan self-leadership merupakan intervensi psikologis yang efektif untuk memperkuat resiliensi kerja karyawan Generasi Z. Penelitian ini memberikan kontribusi empiris terhadap pengembangan intervensi berbasis psikologi organisasi serta menawarkan alternatif strategi pengembangan sumber daya manusia yang adaptif guna mendukung keberlanjutan kinerja pada perusahaan berbasis teknologi digital.